Diversité et dynamique des communautés de protistes dans le haut Arctique canadien - Charvet, Sophie (Université Laval, 2013)
The Arctic region is a blend of stark windswept landscapes interwoven with a wide diversity of freshwater ecosystems. Presently confronted by temperature increases well above global average, causing changes in landscape and aquatic properties, the Arctic is a strategic area to study the impact of climate change on endogenous microbial communities. Ice is a crucial characteristic of Arctic ecosystems and has already begun to cross thresholds along the northern coastline of Ellesmere Island. In lakes, the effects of cold temperatures, variable irradiance and low inorganic nutrients combine to restrict primary production and growth of most organisms. The established richness of microorganisms present in these systems is due to the high diversity of their adaptive and nutritive strategies. Hence, the observed shifts in ice cover regimes of lakes will have impacts on their biological activity. Of these microbial components, the protists, unicellular eukaryotes, exploit a wide range of carbon and energy resources from phototrophy to predation and the combination of both, mixotrophy. The subject of this research was to determine the contribution of mixotrophs to protist community structure in Arctic lakes, and to develop knowledge of their potential response to the changing environmental conditions. Char Lake, Lake A and Ward Hunt Lake, three limnologically different lakes, were chosen to investigate the biodiversity of protists in August 2008. Microscopy, pigments and 18S gene clone libraries revealed a dominance of each lake by chrysophytes, prominent mixotrophic protists. At Lake A, the summer of 2008 was marked by a loss of ice-cover, creating atypical open-water conditions. High-throughput sequencing of the V4 region of the 18S ribosomal RNA gene revealed the contrast between the homogenous community structure within the ice-covered water column of May 2008, despite the sharp physico-chemical meromictic stratification within the lake, and the established spatial variability of the protist communities under the ...